Ringworm Resolved With Pulsatilla – An Evidence Based Case Report (Homoeopathy for All, 2025)
Tinea corporis (TC)  is the most prevalent superficial  fungal infection of the skin, caused  by dermatophytes that colonize  and thrive on dead keratin within  the epidermis. This condition is  characterized by distinctive ring shaped lesions, often accompanied  by itching, redness, and discomfort.  Various environmental factors,  including excessive heat, high  humidity, and tight-fitting clothing,  create favorable conditions for  fungal proliferation, exacerbating  the infection and increasing the  likelihood of recurrence. The  persistent nature of TC not only  leads to physical distress but also  affects a patient’s psychological  well-being, self-confidence, and  overall quality of life. Therefore,  effective treatment approaches that  target both the underlying cause  and aggravating factors are crucial  for long-term relief and improved  patient outcomes. Case Summary: This case of TC, with extensive  spread on the body, demonstrates  the curative effect of homoeopathic  medicine. A 40 year-old female  diagnosed with TC was treated  successfully with individualised  homoeopathic medicine for six  months. The outcome was assessed  through before-and-after-treatment  photographs. The case has been  reported as per HOM-CASE  guidelines. A complete alleviation of  TC was observed with homoeopathic  medicine pulsatilla.
Keywords: Individualised Homoeopathy; Pulsatilla; Tinea corporis; Ringworm